2015
DOI: 10.1016/j.worlddev.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Does Shelter Assistance Reduce Poverty in Afghanistan?

Abstract: Forced migration, often resulting from violent conflict, imposes large economic costs on both sending and receiving countries, on those agencies that coordinate humanitarian services and most importantly upon the forced migrants themselves. Programs encouraging the return of refugees are therefore potentially crucial interventions, which can result in all parties benefiting. In this paper, we assess the UNHCR post-return shelter assistance program in Afghanistan between 2009 and 2011, the country most affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
“…As Table 1 shown, we collected data from the six groups of stakeholders and then we placed them into five categories: None or few (0-20), not too much (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), neutral (41-60), partial (61-80), and very much (81-100). Among the 2563 responses related to the DAC, 62 people (2.4%) realized that the Afghan Government has no or few DACs to influence the development process of the Aynak Copper Mine, and 524 (20.4%) considered that there is not too much the DAC of the Afghan Government can do with the development of the Aynak Copper Mine.…”
Section: Variable Definitionsmentioning
confidence: 99%
“…We fill this research gap by providing some of the first clear, rigorous quantitative evidence on these policies. 1 In the spirit of recent literature designed to assess the impact of specific development programs (Bezu, Kassie, Shiferaw, & Ricker-Gilbert, 2014;Jodlowski, Winter-Nelson, Baylis, & Goldsmith, 2016;Larsen & Lilleør, 2014;Loschmann, Parsons, & Siegal, 2015;Mendola & Simtowe, 2015), we formulate our research question as a test of the impact of diversity in crop cultivation on household poverty in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…For the past decade, Afghanistan has consistently been one of the main countries of origin receiving returnees globally (Majidi 2017). In 2011, around one-third of the population in Afghanistan were returnees (Loschmann et al 2015). Despite their large population, the living situation of Afghan returnees is one of the most understudied areas in the forced migration field (Majidi 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among minimum standards of living, access to a covered living area is a fundamental human need and an essential element in the provision of protection, dignity, and identity for returnees (Babister and Kelman 2002). Moreover, access to a covered living area could be an essential element for households' livelihood and socio-economic development (Babister and Kelman 2002;Crea et al 2017;Loschmann et al 2015). In the harsh winters and hot summers of Afghanistan, access to shelter could be a crucial factor for survival.…”
Section: Introductionmentioning
confidence: 99%